Step-by-step Solution

Solve the equation $\left(x+1\right)\left(x-2\right)=0$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Final Answer

$x+1=0,\:x-2=0$

Step-by-step Solution

Problem to solve:

$\left(x+1\right)\left(x-2\right)=0$
1

Break the equation in factors and set each equal to zero, to obtain

$x+1=0,\:x-2=0$
2

Solve the equation ($1$)

$x+1=0$
3

Solve the equation ($2$)

$x-2=0$
4

The $2$ solutions of the equation are

$x+1=0,\:x-2=0$

Final Answer

$x+1=0,\:x-2=0$